Evaluation of the Soda Tax on Obesity and Diabetes in California: A Cost-Effectiveness Analysis - Fan Zhao; Risha Gidwani; May C. Wang; Liwei Chen; Roch A. Nianogo (MDM Policy & Practice)
Introduction. Consumption of sugar-sweetened beverages (SSBs) contributes to weight gain, obesity, and diabetes. Soda tax has been proposed to reduce consumption of SSBs. What remains unclear is whether the soda tax has an effect on health and health care costs. We evaluated the cost-effectiveness of a 1-cent-per-ounce soda tax on obesity and diabetes in California. Methods. A microsimulation state-transition model was used to evaluate the cost-effectiveness of the soda tax. Health outcomes were measured in quality-adjusted life-years (QALYs). Health care costs were projected from 2015 to 2035. Results. In a simulated cohort of Californian adults, the soda tax policy prevented 2.28 million cases of overweight (95% confidence interval [CI] −0.06 to 6.63) and 0.49 million cases of obesity (95% CI −0.19 to 1.18). From the health care perspective, the incremental cost-effectiveness ratio of the soda tax was $124,839 dollars per QALY (95% CI −1,151,983 to 557,660). From the health care perspective, the soda tax policy was cost-effective 80% of the time in the probabilistic sensitivity analysis using a willingness-to-pay threshold of $100,000 per QALY. Conclusions. The 1-cent-per-ounce soda tax reduced the number of obesity cases, diabetes cases, and related complications. In addition, the soda tax policy implemented in California was cost-effective most of the time. Highlights Question: What remains unclear is whether the soda tax has an effect on health and health care costs. Findings: The 1-cent-per-ounce soda tax reduced the number of obesity cases, diabetes, and related complications. In addition, the soda tax policy brought large amounts of revenue. Meaning: This study provides additional evidence regarding the health care costs and cost-effectiveness related to the implementation of a soda tax.